Corn and soybean grain yield responses to soil amendments and cover crop in upland soils. (26th November 2019) - Adeli, Ardeshir; Brooks, John P.; Read, John J.; Feng, Gary; Miles, Dana; Shankle, Mark W.; Jenkins, Johnie N.
Abstract: A field study was conducted on upland soils for six years to determine interactive effects of winter wheat ( Triticum aestivum L.) cover crop, organic and inorganic soil amendments on grain yields and nutrient utilizations in a no-till corn ( Zea mays )-soybean ( Glycine max ) rotation. Experimental design was a split-plot arrangement with four replicates. Cover crops were the main plots and fertilization treatments used as sub-plot. Fertilization treatments included an unfertilized control, poultry litter, poultry litter (PL) plus flue gas desulfurization (FGD) gypsum and inorganic N fertilizer applied every other year to corn. Corn grain yield and grain N and P uptake were greater with PL than inorganic fertilizer in 2014 and 2016. Addition of FGD gypsum to PL significantly increased corn grain yield by 15% in 2016. Cover crop increased corn and soybean grain yields in a year with less seasonal rainfall possibly by conserving soil moisture.